Mitochondrial-generated ROS down regulates insulin signaling via activation of the p38MAPK stress response pathway. (5th January 2016) - Al-Lahham, Rabab; Deford, James H.; Papaconstantinou, John
Abstract: Impairment of insulin signaling and hepatic insulin resistance has been attributed to ROS-mediated activation of p38MAPK stress response signaling. Our research focused on whether (a) ROS generated by mitochondrial electron transport chain complex I (ETC-CI) dysfunction, via the use of Rotenone, inactivates insulin signaling; and (b) the p38MAPK pathway is involved in the ROS-induced impairment of insulin signaling. Our results show that in primary mouse hepatocytes the CI inhibitor, Rotenone, (a) induces IRS-1 Ser 307 phosphorylation that is blocked by the anti-oxidant NAC or by the p38MAPK inhibitors, SB203580 and SB202190; (b) inhibits insulin-stimulated AKT-Ser 473 and GSK3β-Ser 9 phosphorylations, in a manner that is not responsive to reversal by the anti-oxidant NAC or by the p38MAPK inhibitors, SB203580 and SB202190. We conclude that rotenone-induced insulin resistance involves a p38MAPK-dependent mechanism for the inhibition of the proximal end of insulin signaling (IRS1), and a p38MAPK-independent mechanism for the inhibition of the distal end (AKT and GSK3β). Our study suggests that ROS generated by inhibition of ETC CI, promotes hepatic insulin resistance partly via activation of the p38MAPK stress-response pathway. Graphical abstract: Highlights: ROS generated by electron transport chain complex CI (ETC-CI) promotes hepatic insulin resistance via p38MAPK . The mechanism of Rotenone-mediated impairment of insulin signaling. Dysfunctional mitochondrial ETC-CI impairs insulin signaling. Rotenone, inactivates IRS-1, AKT(PKB) and GSK3β by inducing phosphorylation of specific serine residues.